Increased photocurrent response in Nb-doped TiO2 nanotubes - Yang, Mingjun; Jha, Himendra; Liu, Ning; Schmuki, Patrik (Journal of Materials Chemistry, 2011)
Nb-doped TiO2 nanotube (NT) layers were grown by electrochemical anodization of Ti–Nb alloys. To successfully activate Nb doping the oxide tubes need to be annealed at sufficiently high temperatures (650 °C). For tubes doped with 0.1 wt% Nb not only a considerable increase in the electrical conductivity but also a significantly enhanced photocurrent (superior to any pure TiO2 nanotube layer (anatase or rutile)) was obtained.
EAM Import::2019-03-13